2022
DOI: 10.4103/jehp.jehp_374_21
|View full text |Cite
|
Sign up to set email alerts
|

Assessing vaccine hesitancy among health-care workers in Jammu and Kashmir

Abstract: BACKGROUND: The World Health Organization declared vaccine hesitancy as one of the planet's top 10 global health threats in 2019. With the rollout of the coronavirus disease-19 (COVID-19) vaccines, a survey was conducted to find out the hesitancy and the apprehensions that come along with taking COVID-19 vaccines among health-care workers (HCWs). MATERIALS AND METHODS: This was an online cross-sectional survey which was developed and shared through soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…There has also been low acceptance rates among HCWs in the Democratic Republic of Congo (27.7%) [ 65 ], 42.7% to 51.3% in different studies in Ethiopia [ 66 , 67 , 118 ], and 57% to 63.8% among HCWs in Sudan [ 68 , 121 ]. The rate in our study is also higher than 59% found in one study in South Africa [ 69 ], 54.6% to 67.7% among HCWs in India [ 122 , 123 ], 68.6% among HCWs in Turkey [ 124 ] and 69% in the global survey by Noushad et al [ 55 ].…”
Section: Discussioncontrasting
confidence: 66%
“…There has also been low acceptance rates among HCWs in the Democratic Republic of Congo (27.7%) [ 65 ], 42.7% to 51.3% in different studies in Ethiopia [ 66 , 67 , 118 ], and 57% to 63.8% among HCWs in Sudan [ 68 , 121 ]. The rate in our study is also higher than 59% found in one study in South Africa [ 69 ], 54.6% to 67.7% among HCWs in India [ 122 , 123 ], 68.6% among HCWs in Turkey [ 124 ] and 69% in the global survey by Noushad et al [ 55 ].…”
Section: Discussioncontrasting
confidence: 66%
“…Shah NN conducted a survey among healthcare professionals in Kashmir and reported that being unmarried was strongly linked to a higher incidence of vaccine reluctance. The three biggest significant drivers of vaccine opinions were doubts regarding the vaccine’s effectiveness, unanticipated issues in youngsters, and potential upcoming harmful vaccine impacts [ 32 ]. In the study by Jose S. et al among healthcare workers in North India, most people (62%) expressed apprehension about the vaccine’s reliability, including potential risks, manufacturing assurance, and vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“… Acceptance of the COVID-19 vaccine in India according to residence, as shown in the form of a forest plot [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. …”
Section: Figurementioning
confidence: 99%